The ZEW Financial Market Survey panel - Frank Brückbauer; Michael Schröder (Journal of Economics and Statistics, 2023)
The ZEW Financial Market Survey is a monthly panel survey among financial market experts that was launched in December 1991. The survey focuses on the experts' expectations about international financial markets and macroeconomic developments. We describe the ZEW Financial Market Survey and the resulting research dataset, which is available for free for academic researchers, is large and includes long individual time series (99,001 responses by 2002 respondents, as of September 2021), and contains rich information on the financial market experts collected over the years and which can be combined with the data on expectations.
Keywords: C8; D84; G17; G4; 330; financial market expectations; financial market experts; ZEW Financial Market Survey